ANALISIS GAYA BAHASA RETORIS DALAM PIDATO BUNG KARNO - Lubis, Mina Syanti (JURNAL EDUCATION AND DEVELOPMENT, 2017)
The purpose of speech is not only give information to the public verbally but speech should pay attention language, diction, and style that used so that the information can be received by audience. the style of language is one of the things taht need to be considered in giving speech because the beauty in using style of language is a hallmark of a good speech. Ir. Soekarto (the firs president of indonesia) was a capable rhetorical to build and burn the spirit of Indonesian youth to be independent and irrespective of the other colonies of the nations. Nationalism, the burning spirit of the youth, an the maintenance of the nation"s self-esteem, are the preice of every speech. until today the refernce to speech still refers to him. based on the nanalysis,  the rhetorical languange that used Ir. Soekarno in his speech was anastrop as many as 5 quotations, apostrophes as many as 3 quontations, asindeton as many as  1 quotation, and polisidenton as many as 7 quotations. the purpose of using of rhetorical language is to affirm something so rise the spirit of the audience, showing a pround impression of a struggle that expressed by using the figure of speech.